Macro and Micro Characteristics of Extreme Heavy Rainfall Process in Jincheng of Shanxi Province on 11 July 2021 - Hongxia WANG; Aimei MIAO; Guiqiang QIU; Zhiyong QU; Junmei YANG; Linyi LÜ (Gaoyuan qixiang)
Using ERA5 reanalysis data， automatic weather station data， FY4A satellite data， Doppler radar and Laser raindrop spectrometer data， the macro and micro characteristics of the extreme rainfall process in Jincheng， Shanxi Province on July 11， 2021 are analyzed. The results show that： （1） This extreme rainfall in Jincheng is the second highest rainfall in July since 1961. The strong divergence on the right of the upper jet entrance， the convergence of wind speed at the exit of lower jet， and the strong convergence near the warm shear line of the low vortex are the macro dynamic conditions of the extreme rainfall. The water vapor transfer by the low-level jet and the whole layer precipitable water above 65 mm， are the macro water vapor conditions， while 500 hPa trough is ahead of the cold shear lines on 700 hPa and 850 hPa is the macro dynamic unstable condition for this extreme heavy rainfall. （2） The extreme heavy rainfall is located in an irregular quadrilateral area surrounded by 500 hPa trough， 850 hPa and 700 hPa warm shear lines and ground dry line， which overlaps with the areas controlled by 500 hPa T-Td≤4 ℃， 700 hPa T-Td≤3 ℃， 850 hPa T-Td≤2 ℃， K index≥38 ℃ and Si index≤-1 ℃. The maximum extreme precipitation occurs in the large value area of the brightness temperature gradient on the southwest side of the convective cloud cluster and the low brightness temperature area in the southwest of the cloud cluster， which is within 0~30 km of the surface dry line and surface mesoscale shear lines. （3） The meso-α-scale warm shear line on 850 hPa， ground dry line and meso-β-scale surface shear lines and convergence lines triggered this extreme heavy rainfall in Jincheng. The strengthened easterly air flow on the surface layer is forced to converge and lift when it meets the trumpet shaped terrain opening eastward formed by Zhongtiao Mountain， Wangwu Mountain， Xionger Mountain and Song Mountain， promoting the convergence and rising movement in extreme precipitation areas and increasing the precipitation. （4） The lightning is located in the area where the cloud top brightness temperature is ≤220 K and the large value area of cloud top brightness temperature gradient. The peak value of lightning frequency is 10~35 minutes ahead of the peak value of precipitation， which is very significant for early warning of precipitation peak value. （5） The meso-α-scale low vortex warm shear system stimulates the development of the meso-α-scale vortex cloud system. The development and evolution of convective cloud clusters are backward development type. In the meso-α-scale vortex warm shear line cloud system， there are several organized meso-γ-scale convective cells with independent echo， which are guided by the southwest air flow moving to the northeast and form a train effect in the extreme precipitation area. The convective cell that leads to the largest rain peak in Manghe scenic area has the typical supercell storm structural characteristics. （6） The significant increase of cloud water content promotes the enhancement of precipitation intensity， and the high area of supercooled water content in -20~0 ℃ layer corresponds to the extremely heavy precipitation area on the ground. The extreme precipitation in Jincheng is stratiform and cumulus mixed cloud precipitation， and the particle size distribution of raindrops is wide. Small and medium raindrops with high concentration are the main contributors of extreme heavy precipitation. Compared with the typical continental convective precipitation process， the average range of the average generalized intercept common logarithm （lg（NW）） of raindrops in this extreme heavy precipitation process is large， but the mass weighted average diameter （DM） is slightly smaller than the average range.